Panorama Kitab Hukum Kanonik: (Tinjauan Tempat, Peran dan Fungsi di dalam Gereja Katolik) - Nikodemus Nikodemus; Yohanes Endi (Jurnal Pendidikan Agama dan Teologi, 2024)
The focus of this study is to understand the Book of Canon Law as the internal legal basis of the Catholic Church which regulates ecclesiastical governance and discipline. In the context of its place, the Book of Canon Law has a central role as an instrument that regulates various aspects of ecclesiastical life, from hierarchical organization to liturgy. Its role extends beyond administrative boundaries, making it an important guide in carrying out pastoral duties and maintaining ecclesiastical discipline. The role of the Book of Canon Law is not only limited to internal ecclesiastical aspects, but also influences the church's relationship with wider society. This book reflects the role of the church in regulating the spiritual and moral life of Catholics and maintaining doctrinal integrity. The function of the Code of Canon Law is also to facilitate conflict resolution and uphold justice among church members. The author uses descriptive analysis methods and the Book of Canon Law as a scalpel to explain the contents of the article that will be discussed. In the midst of dynamic social and cultural change, the Code of Canon Law becomes relevant in interpreting and applying moral and ethical principles, which are appropriate in the contemporary context. The harmony between these principles and the challenges of modern times is an integral part of the role and function of the Code of Canon Law in maintaining the identity and mission of the Catholic Church.